2015
DOI: 10.2139/ssrn.2649928
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Access to Health Insurance for Informally Employed Individuals in Peru

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…Among those 34 studies, 17 found a positive effect (i.e. a reduction in out-of-pocket expenditure), 15 studies found no statistically significant effect, and two studies–from Indonesia[59] and Peru[62]–reported a negative effect (i.e. an increase in out-of-pocket expenditure).…”
Section: Resultsmentioning
confidence: 99%
“…Among those 34 studies, 17 found a positive effect (i.e. a reduction in out-of-pocket expenditure), 15 studies found no statistically significant effect, and two studies–from Indonesia[59] and Peru[62]–reported a negative effect (i.e. an increase in out-of-pocket expenditure).…”
Section: Resultsmentioning
confidence: 99%
“…However, lack of budgeting for the projected costs of delivering the benefit package, the continued exclusion of salary costs from the reimbursement rates, poor access to facilities in rural areas, manpower shortages, ineffective medicines procurement and widespread lack of inputs necessary for surgery mean that the service coverage actually available is likely to have fallen well short of that promised (Francke 2013;Vermeersch, Medici, and Narvaez 2014;Bernal, Carpio, and Klein 2015). Effective coverage of inpatient treatment was likely to have been particularly limited.…”
mentioning
confidence: 99%
“…Importantly, their results do not show any improvements in health status. Bernal et al (2014) examine the impact of Peru's "Seguro Integral de Salud," which provides insurance coverage to individuals employed outside the formal labor market, on healthcare use and health indicators. Using a fuzzy regression discontinuity design to address the program endogeneity, the authors 9 They also examine the impact of the reform on supply-side responses and show that although the number of hospital beds went up, the number of medical institutions, physicians, and nurses did not seem to increase due to the reform.…”
Section: Literaturementioning
confidence: 99%
“…Many countries have taken a primarily demand-side approach to extending health coverage, through mechanisms such as health insurance, user-fees on the basis of ability-to-pay, and conditional cash transfers, for example China (Carrin et al, 1999;Wagstaff et al, 2009), Colombia (Arroyave et al, 2013Giedion and Diaz, 2010;Ruiz et al, 2007), Costa Rica (Cercone et al, 2010;Dow and Schmeer, 2003), Mexico (Pfutze, 2014;Sosa-Rubi et al, 2009), Peru (Bernal et al, 2014;Bitrán et al, 2010), Taiwan (Cheng and Chiang, 1997), and Vietnam (Ekman et al, 2008;Somanathan 1 Opening remarks at a member state consultation on health in the post-2015 development agenda Geneva, Switzerland. , 2013).…”
mentioning
confidence: 99%